ISSUES OF UNIFIED TELEMEDICINE COUNSELLING - J. G. Astashevich; V. A. Lapickyj; D. L. Pinevich; S. M. Poljakov; M. M. Sachek (Informatika)
The questions of the construction and operation of the unified telemedicine electronic consulting system are considered, as well as relevant directions of telemedicine consultations development.